2006
DOI: 10.1088/0960-1317/16/9/004
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient 3D micromixer using soft PDMS bonding

Abstract: This paper presents a novel highly efficient passive micromixer that employs diffusion for micromixing. Since conventional fabrication methods cannot form precise aligned microchannels, the realization of a complex 3D micromixer has been difficult. Here, we report a novel micromixer, named a chessboard mixer. In addition, a new polydimethylsiloxane (PDMS) bonding method was developed to produce the proposed mixer. The new PDMS bonding technique requires PDMS-to-PDMS bonding and the moldable flexibility of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 21 publications
0
44
0
Order By: Relevance
“…It was shown that their mechanism of fluid multilamination and elongation is highly effective in enhancing the mass transfer. Cha et al [12] proposed a 3D micromixer combining the focusing and split-and-recombination (SAR) functions called the chessboard mixer (Figure 8). For the flow rate of 12.7 µL/min, 90% of mixing occurs only within the length of 1.4 mm.…”
Section: Hydrodynamic Focusingmentioning
confidence: 99%
“…It was shown that their mechanism of fluid multilamination and elongation is highly effective in enhancing the mass transfer. Cha et al [12] proposed a 3D micromixer combining the focusing and split-and-recombination (SAR) functions called the chessboard mixer (Figure 8). For the flow rate of 12.7 µL/min, 90% of mixing occurs only within the length of 1.4 mm.…”
Section: Hydrodynamic Focusingmentioning
confidence: 99%
“…After the BOE, inductive coupled plasmas (ICP) dry etching is used to etch 230 µm deep channels and valves in the silicon. Here, the standard Bosch process is applied [40,41], which makes high aspect ratio silicon structures with vertical sidewalls possible [42]. Finally, the low pressure SF 6 plasma generated by a radio-frequency (RF) source is used to clean the C 4 F 8 deposition layer on the substrate and the walls of the channel and the valve.…”
Section: Design Of the Systemmentioning
confidence: 99%
“…In order to enhance mixing, various ideas have been proposed in the literature. Cha et al (1) , e.g., proposed a three-dimensional micro-mixer combing the focusing and split and recombination functions called the 'chessboard' mixer. Suh et al (2) presented a new design channel composed of a series of cross baffles within a channel.…”
Section: Introductionmentioning
confidence: 99%